Padrão de poder colonial: síntese e futuro Sobre o artigo de Aníbal Quijano: “Colonialidade de poder, cultura e conhecimento na América Latina”, 1999 - Ortega, Pedro José (2023)
The work of Aníbal Quijano has played a pivotal role in bridging the gap between dependency theory and the decolonial movement. This premise finds its primary foundation in Quijano’s seminal article, “Coloniality of Power, Culture, and Knowledge in Latin America.” In this article, Quijano elucidates the historical evolution of the “pattern of colonial power,” a concept of profound significance and widespread recognition within decolonial discourse. For the sake of didactic clarity, this exposition distills three fundamental aspects of the colonial power pattern. These aspects not only elucidate the intricate connection between dependency and decoloniality but also delineate the overarching themes of the decolonial movement. These themes encompass a critique of modernity, Eurocentrism, and individualist capitalism, culminating in the articulation of a Latin American utopia struggling to establish its own legitimacy for critical examination. This, in turn, paves the way for a reconfiguration of the epistemic framework necessary for emancipation and social liberation. The three core facets of the decolonial current, as expounded in this article, include: a) The Intersection of Race and the Colonial Power Pattern, b) Subalternity and Its Relationship to Imitation, c) Eurocentric Hegemony and the Nexus of Material and Subjective Dependence. This article, while concluding with an open-ended perspective, underscores the enduring influence of Aníbal Quijano’s legacy within the realm of decolonial scholarship.